2017
DOI: 10.2503/hortj.okd-057
|View full text |Cite
|
Sign up to set email alerts
|

<i>LhMYB12</i>, Regulating Tepal Anthocyanin Pigmentation in Asiatic Hybrid Lilies, is Derived from <i>Lilium dauricum</i> and <i>L. bulbiferum</i>

Abstract: Genes encoding a MYB12 transcription factor, which regulates anthocyanin biosynthesis, are the key genes causing variations in the anthocyanin colors in lily flowers. However, the origin of the MYB12 in Asiatic hybrid lilies (Lilium spp.) is not completely known. In this study, we analyzed anthocyanin pigments in tepals of L. maculatum, L. lancifolium, L. callosum, L. leichtlinii, L. davidii, L. bulbiferum, and L. dauricum, and clarified that L. dauricum and L. bulbiferum accumulated a single anthocyanin, cyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 23 publications
(24 reference statements)
1
7
0
Order By: Relevance
“…In lily hybrids, origin lily species were identified using nucleotide sequence alignments of the MYB12 gene that regulates anthocyanin accumulation in tepals. In lilies, Asiatic and Oriental inter-specific hybrid cultivar groups are differentiated with respect to polymorphisms of MYB12 (Yamagishi et al, 2014;Yamagishi and Nakatsuka, 2017). Similarly, we found that nucleotide sequence alignments of the F3'5'H gene of wild species and cultivars are different, resulting in F3'5'H gene polymorphisms.…”
Section: Phylogenetic Relationship Of the F3'5'h Gene Among Wild Specsupporting
confidence: 53%
“…In lily hybrids, origin lily species were identified using nucleotide sequence alignments of the MYB12 gene that regulates anthocyanin accumulation in tepals. In lilies, Asiatic and Oriental inter-specific hybrid cultivar groups are differentiated with respect to polymorphisms of MYB12 (Yamagishi et al, 2014;Yamagishi and Nakatsuka, 2017). Similarly, we found that nucleotide sequence alignments of the F3'5'H gene of wild species and cultivars are different, resulting in F3'5'H gene polymorphisms.…”
Section: Phylogenetic Relationship Of the F3'5'h Gene Among Wild Specsupporting
confidence: 53%
“…Anthocyanin biosynthesis in lilies is mainly regulated by the MYB12 transcription factor through activation of anthocyanin structural genes (Yamagishi and Nakatsuka, 2017). In this study, we analysed the potential functions of anthocyanin structural genes F3'H, DFR, ANS and transcription factor MYB12 in stimulating anthocyanin biosynthesis in lilies.…”
Section: Discussionmentioning
confidence: 99%
“…In the green tissue General Discussion like leaves, anthocyanin accumulation might have been masked by chlorophyll and variation in vacuolar pH during leaf development might cause the loss of anthocyanin contents (Wei et al, 2017). However in flower tissue, other MYB-like transcription factors such as MYB12 and MYB15 have been shown to induce anthocyanin accumulation in the Asiatic and Oriental hybrid lily tepals (Yamagishi and Nakatsuka, 2017;Yamagishi, 2016;2011). It was speculated whether the change of flower colour in transformed lily will remain stable, as demonstrated in the flowers of transformed N. benthamiana (Chapter 3).…”
Section: Genetic Modification Of Flower Colourmentioning
confidence: 98%
See 2 more Smart Citations